The Effect of Globe Teaching Aids on Elementary Students’ Social Science Literacy in Map Materials - Anggi Sulistiyowati; Herniyanti Herniyanti (Research, Training and Philanthropy Institution Natural Aceh, 2026)
This study investigates the effect of globe teaching aids on elementary students' Social Science literacy, particularly in understanding map materials. The need for this Research arises from Indonesia's low literacy performance in PISA 2022, which underscores the urgency of implementing more effective and engaging learning strategies. A quasi-experimental design was used, involving two groups and 30 students in total. The experimental group received instruction using globe teaching aids, while the control group was taught through conventional methods. The findings show a significant improvement in students' Social Science literacy among those who were taught using globes, as indicated by posttest differences between the two groups (p < 0.05). The normalized gain score further demonstrates the intervention's effectiveness, with the experimental group achieving a gain of 0.734 compared to 0.337 in the control group. These results indicate that using globes not only enhances students' comprehension of spatial relationships but also strengthens their overall map literacy. The study highlights the importance of integrating concrete and interactive learning tools in Social Science instruction. The findings provide practical implications for educators, suggesting that globe teaching aids can serve as an effective alternative to improve students’ literacy and engagement in learning map concepts.